ASEAN and the EU Challenged by “Divide and Rule” Strategies of the US and China Evidence and Possible Reactions - Suthiphand Chirathivat; Rolf J. Langhammer (International Economics and Economic Policy, 2020)
The US and China have launched attacks upon the coherence of the Association of Southeast Asian Nations (ASEAN) and the European Union (EU) by offering individual member states privileges if they depart from common policies of the two integration schemes. The article describes the motivation behind these offers and the ways how they are addressed to the member states. It sees such “divide and rule” policies as serious challenges for the collective bargaining power the ASEAN and the EU and discusses strategies to counter these challenges. For both the US and China, the authors see economic and political targets as the main motivation. Economically, each of the two countries wants to gain superiority in pathing free ways for their suppliers of technology, goods and services to the markets of the two schemes against the competitive pressure of the other country. Politically, the two schemes have become contested areas in geopolitical struggles between the two countries. For the EU as the more advanced scheme of deep integration, the paper recommends a closer convergence between EU policies and the demand of the electorate, to prefer more cooperation projects over deeper integration steps and to motivate the private sector, in particular foreign investors to stand up against “divide and rule “strategies. For ASEAN, it is important to see the Sino-US conflict as a long term challenge, to prevent the region from becoming a Chinese backyard, and to deepen integration by removing non-tariff barriers to trade within ASEAN.
Keywords: F01; F15; O52; O53; 330; Regional integration; Cooperation; External challenges; US-China conflict; Brexit; Asia; Trade